A study on the constraints to reaching the hardcore poor with microcredit - De Costa, Nicholas; Association for Social Advancement (Dhaka, Bangladesh) (Dhaka : Association for Social Advancement, 1997)
Relates to Nilphamari District, Bangladesh.
Includes bibliographical references (p. 56).
Keywords: Microfinance -- Bangladesh; Microfinance; Poor -- Bangladesh